Ferroelectric composite structure, method of making and use thereof

CN122803365APending Publication Date: 2026-09-22INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610789492.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0007]本发明的一个目的在于提供一种具有高剩余极化强度、低漏电流、高耐压性能的铁电复合结构,以克服现有单一相PbTiO3铁电薄膜剩余极化强度不足、易击穿等问题

Benefits of technology

[0029](1)显著提高剩余极化强度:通过引入非晶保护层,本发明铁电复合结构的剩余极化强度可达到80~500 μC/cm2,远高于传统单一相PbTiO3薄膜(通常<60 μC/cm2)以及多数复合结构PbTiO3材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122803365A_ABST
    Figure CN122803365A_ABST
Patent Text Reader

Abstract

The application provides a ferroelectric composite structure and a preparation method and application thereof. The composite structure comprises a PbTiO3 ferroelectric film layer with a perovskite structure and an amorphous protective layer formed on the upper surface of the PbTiO3 ferroelectric film layer. The protective layer is formed by pyrolysis of a precursor material used for forming the PbTiO3 ferroelectric film layer and is not subjected to crystallization annealing treatment. The residual polarization of the composite structure can reach 80-500 μC / cm 2 and has the advantages of low leakage current, high voltage resistance and the like. The preparation method comprises the following steps: preparing a PbTiO3 ferroelectric film layer on a substrate through multiple spin-coating-pyrolysis and high-temperature crystallization annealing, spin-coating a precursor on the PbTiO3 ferroelectric film layer and pyrolyzing the precursor at 120-400 DEG C for 5-30 min to form an amorphous protective layer, and not performing crystallization annealing. The method is simple in process and low in cost, and the obtained ferroelectric composite structure can be used in ferroelectric memories, ferroelectric logic devices and low-power electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ferroelectric materials. Specifically, this invention relates to ferroelectric composite structures, their preparation methods, and applications. Background Technology

[0002] With the rapid development of artificial intelligence, big data, and the Internet of Things, the global data volume is growing exponentially, posing unprecedented challenges to the energy efficiency, speed, and integration of data storage and processing systems. Traditional silicon-based memory and logic devices are limited by inherent physical bottlenecks (such as leakage current, Joule heating, and charge transfer delay), making it difficult to meet the future application requirements for low power consumption and high-speed response.

[0003] Ferroelectric materials have attracted much attention due to their unique spontaneous polarization properties: their polarization direction can be reversibly flipped under an applied electric field and stably maintain two or more polarization states (corresponding to "0" and "1" in binary logic) after the electric field is removed. Since polarization flipping does not involve charge transport, it is theoretically possible to achieve ultra-low power consumption and ultra-fast read / write speeds. Therefore, ferroelectric materials are considered core candidate materials for building next-generation non-volatile memories and ultra-low power logic devices.

[0004] In recent years, researchers have been working to improve the macroscopic ferroelectric properties of ferroelectric materials through various strategies such as strain engineering, doping modification, interface modulation, and external field excitation. For example, AlScN thin films obtained by doping AlN semiconductors with Sc exhibit large remanent polarization and high breakdown voltage. However, Sc is expensive, and AlScN thin films suffer from poor fatigue characteristics and short cycle life. Another classic ferroelectric material is lead zirconate titanate (PZT), which has excellent ferroelectric properties, but even small fluctuations in the Zr / Ti ratio can significantly affect its electrical properties, making it difficult to guarantee the uniformity of mass production. At the same time, PZT has a low Curie temperature (typically 300–400 °C), limiting its application in high-temperature environments.

[0005] Perovskite lead titanate (PbTiO3) is an important ferroelectric material widely used in ferroelectric, piezoelectric, and dielectric devices. Studies have shown that by constructing PbTiO3-based composite materials, the remanent polarization can reach as high as 236 μC / cm. 2 However, composite phase structures often introduce interfacial instabilities, leading to decreased device reliability. On the other hand, due to substrate lattice mismatch and epitaxial growth constraints, the fabrication of PbTiO3 ferroelectric thin films with a single perovskite phase and high remanent polarization intensity still faces significant technical challenges.

[0006] Therefore, how to further improve the residual polarization intensity, reduce leakage current and enhance the withstand voltage performance of single-phase PbTiO3 ferroelectric thin films without introducing complex composite structures, while taking into account the simplicity of the process, low cost and scalability, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0007] One objective of this invention is to provide a ferroelectric composite structure with high remanent polarization, low leakage current, and high withstand voltage, so as to overcome the problems of insufficient remanent polarization and easy breakdown of existing single-phase PbTiO3 ferroelectric thin films.

[0008] Another objective of this invention is to provide a simple, low-cost, and easily mass-producible method for preparing ferroelectric composite structures. By introducing an amorphous protective layer, the ferroelectric performance is significantly improved, and its application in ferroelectric memories, logic devices, and low-power electronic devices is expanded.

[0009] To achieve the above objectives, the present invention provides the following technical solution.

[0010] In a first aspect, the present invention provides a ferroelectric composite structure comprising: a perovskite-structured PbTiO3 ferroelectric thin film layer; and an amorphous protective layer formed on the upper surface of the perovskite-structured PbTiO3 ferroelectric thin film layer. The protective layer is formed by pyrolysis of a precursor material used to form the perovskite-structured PbTiO3 ferroelectric thin film layer, and is not subjected to crystallization annealing treatment.

[0011] The inventors of this application unexpectedly discovered that by coating the surface of a perovskite PbTiO3 ferroelectric thin film that has already undergone crystallization annealing with the same precursor material and performing only low-temperature pyrolysis (without high-temperature crystallization annealing), the resulting amorphous thin layer does not simply increase the thickness. Instead, it significantly suppresses the recovery behavior of ferroelectric domains after the removal of the external electric field, while substantially reducing leakage current and improving the film's withstand voltage. Although this amorphous protective layer and the underlying crystalline ferroelectric layer have the same chemical composition, the difference in their structural states ("crystalline" versus "amorphous") produces a synergistic enhancement effect, resulting in the overall ferroelectric composite structure having a remanent polarization intensity far exceeding the performance limits of existing single-phase PbTiO3 thin films.

[0012] Preferably, the thickness of the perovskite-structured PbTiO3 ferroelectric thin film is 200–800 nm. This thickness range ensures sufficient polarization charge density while avoiding cracking and stress problems caused by excessively thick films. Representative values ​​include 200 nm, 350 nm, 500 nm, 650 nm, and 800 nm. When the thickness is below 200 nm, the film leakage current is significant; when it is above 800 nm, cracking and stress problems occur.

[0013] Preferably, the thickness of the amorphous protective layer is 10–60 nm. Representative values ​​include: 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, and 60 nm. If the thickness of the amorphous protective layer is too thick, it will suppress the polarity of the film; if the thickness of the amorphous protective layer is too thin, it will not achieve the effect of improving the polarity of the film.

[0014] Preferably, the amorphous protective layer is formed by pyrolysis of the precursor material at 120–400°C for 5–30 min. Within this temperature range, the organic components in the precursor are fully decomposed, but insufficient to drive PbTiO3 crystallization, thus ensuring that the protective layer remains amorphous. Representative values: pyrolysis temperatures of 120°C, 200°C, 300°C, and 400°C; pyrolysis times of 5 min, 10 min, 20 min, and 30 min. Appropriate selection of these conditions can regulate the density and amorphous network structure of the protective layer, thereby optimizing its effect in suppressing domain recovery.

[0015] Preferably, the remanent polarization of the ferroelectric composite structure is 80–500 μC / cm. 2 Compared to unprotected single-phase PbTiO3 films (typically with remanent polarization <60 μC / cm), 2 The residual polarization intensity of the composite structure of the present invention is significantly improved.

[0016] The ferroelectric composite structure of the present invention may further include a substrate, on which the perovskite-structured PbTiO3 ferroelectric thin film layer is located. The substrate provides support and serves as a bottom electrode for thin film growth. The present invention does not impose any particular limitation on the substrate; conventional substrates in the art are acceptable. For example, the substrate may comprise a Pt layer, a Ti layer, a SiO2 layer, and a Si layer stacked sequentially, wherein the Pt layer is in contact with the perovskite-structured PbTiO3 ferroelectric thin film layer. The Pt layer serves as the bottom electrode, the Ti layer as the adhesion layer, the SiO2 layer as the insulating layer, and the Si layer as the mechanical support layer. This multilayer substrate has the advantages of good conductivity, high thermal stability, and suitable lattice matching with PbTiO3.

[0017] Secondly, the present invention also provides a method for preparing the above-mentioned ferroelectric composite structure, comprising the following steps:

[0018] (1) Provide a substrate;

[0019] (2) A perovskite-structured PbTiO3 ferroelectric thin film layer is prepared on the substrate;

[0020] (3) An amorphous protective layer is formed on the upper surface of the PbTiO3 ferroelectric thin film layer with the perovskite structure.

[0021] Preferably, step (2) further includes:

[0022] (2-1) The precursor material for forming the PbTiO3 ferroelectric thin film layer of the perovskite structure is spin-coated onto the substrate. After each spin-coating, a pyrolysis treatment is performed. This spin-coating-pyrolysis cycle is repeated 1 to 30 times in total. The number of spin-coating cycles determines the total thickness of the ferroelectric thin film layer. Representative values ​​are: 1, 5, 10, 15, 20, and 30 spin-coatings. The pyrolysis temperature after each spin-coating is 120–400℃, and the pyrolysis time is 5–30 min.

[0023] (2-2) The obtained stack is subjected to crystallization annealing to crystallize the ferroelectric thin film layer into a perovskite structure. Preferably, the crystallization annealing temperature is 650-750℃ and the time is 25-50 min. Representative values: 650℃, 700℃, 750℃; 25 min, 35 min, 50 min. This annealing condition ensures that PbTiO3 is completely crystallized into the perovskite phase while avoiding excessive grain growth.

[0024] Preferably, step (3) includes: spin-coating the precursor material for forming the PbTiO3 ferroelectric thin film layer of the perovskite structure onto the PbTiO3 ferroelectric thin film layer of the perovskite structure, and then pyrolyzing it at 120–400°C for 5–30 min to form an amorphous protective layer, without further crystallization annealing. The key to this step is "without further crystallization annealing," thereby ensuring that the protective layer remains amorphous.

[0025] This invention does not impose any particular limitation on the precursor material, and conventional precursor materials in the art can be used. For example, the precursor material is formulated from lead acetate, tetrabutyl titanate, ethylene glycol methyl ether, deionized water, acetic acid, and formamide. Lead acetate provides the lead source, tetrabutyl titanate provides the titanium source, ethylene glycol methyl ether is the solvent, acetic acid is the chelating agent to control the hydrolysis rate, deionized water promotes hydrolysis and polycondensation, and formamide is used as a drying control additive to prevent film cracking. This formulation is a classic formulation for the sol-gel method of preparing PbTiO3, and has the advantages of uniform composition, wide process window, and good reproducibility.

[0026] Thirdly, the present invention also provides the application of the above-mentioned ferroelectric composite structure in the preparation of ferroelectric memories, ferroelectric logic devices or low-power electronic devices.

[0027] Because the composite structure of the present invention has ultra-high remanent polarization, low coercive field, low leakage current and excellent withstand voltage, it is particularly suitable as a storage medium for ferroelectric random access memory (FeRAM), a gate dielectric layer for ferroelectric gate field-effect transistor (FeFET), and various low-power logic circuits and Internet of Things node devices that require non-volatile state maintenance.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) Significantly improves remanent polarization intensity: By introducing an amorphous protective layer, the remanent polarization intensity of the ferroelectric composite structure of the present invention can reach 80-500 μC / cm. 2 The temperature is much higher than that of traditional single-phase PbTiO3 films (typically <60 μC / cm). 2 ) as well as most composite PbTiO3 materials.

[0030] (2) Reduce leakage current and improve withstand voltage performance: The amorphous protective layer has high resistance characteristics, which effectively suppresses the formation of leakage current channels and significantly improves the breakdown electric field of the thin film. The hysteresis loop changes from wide to narrow, the coercive field is reduced, and the reliability of the device is enhanced.

[0031] (3) Simple process and low cost: The present invention adopts the sol-gel method, which does not require complex vacuum equipment, and the precursor raw materials are cheap and readily available. The protective layer and the ferroelectric layer use the same precursor, so no additional materials are required. The entire process can be completed under conventional laboratory conditions, making it easy to achieve large-scale production.

[0032] (4) Stable structure and good repeatability: Since the protective layer and the ferroelectric layer are made of the same material (both are PbTiO3 system), their thermal expansion coefficients are matched, the interface is firmly bonded, and there is no problem of heterogeneous interface diffusion or reaction. After multiple spin coating-pyrolysis-annealing processes, the performance difference between batches is small.

[0033] (5) Broad application prospects: The composite structure of this invention meets the stringent requirements of next-generation high-density, low-power memory and logic devices for ferroelectric materials. At the same time, its preparation method is compatible with existing semiconductor processes, which is expected to promote the industrialization of ferroelectric memory devices. Attached Figure Description

[0034] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings, wherein:

[0035] Figure 1 The X-ray diffraction (XRD) patterns of the ferroelectric composite structures prepared in Examples 1 to 3 of this invention are shown below.

[0036] Figure 2 The diagram shows a comparison of the hysteresis loops (PE loops) of the structures obtained in Embodiment 1 and Comparative Example 1 of the present invention.

[0037] Figure 3 The diagram shows a comparison of the hysteresis loops (PE loops) of the structures obtained in Embodiment 2 and Comparative Example 2 of the present invention.

[0038] Figure 4 This is a comparison diagram of the hysteresis loops (PE loops) of the structures obtained in Embodiment 3 and Comparative Example 3 of the present invention;

[0039] Figure 5 This is a spherical aberration electron microscope (TEM) image of the structure obtained in Example 3 of the present invention. Detailed Implementation

[0040] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention.

[0041] Crystal structure testing: The phase analysis of the thin film was performed using a Bruker D2 Phaser X-ray diffractometer (Cu Kα radiation, λ=0.154184 nm, tube voltage 30 kV, tube current 10 mA, scanning range 20°~60°, step size 0.02°).

[0042] Ferroelectric performance testing: The German TF Analyzer 1000 ferroelectric instrument and AIXACCT were used (test frequency of 1 kHz, applied voltage range of 0-200 V).

[0043] Thickness testing: Cross-sectional scanning was performed using the NEOARM electron microscope (Japan).

[0044] Leakage current test: German TF Analyzer 1000 ferroelectric instrument, aixACCT (maximum applied voltage 12 V, step size 500 mV).

[0045] Example 1

[0046] (The total thickness of the ferroelectric thin film is approximately 200 nm.)

[0047] (1) Preparation of precursor solution

[0048] Weigh 0.4173 g of lead acetate (Pb(CH3COO)2·3H2O) and 345 ml of tetrabutyl titanate (Ti(OC4H9)4), and dissolve them in 4156 mL of ethylene glycol methyl ether, stirring until completely dissolved. Add 100 mL of deionized water and 200 mL of acetic acid as stabilizers and chelating agents. Mix the two solutions and continue stirring for 30 minutes. Finally, add 200 mL of formamide to inhibit cracking, and continue stirring for 2 hours. Allow to stand and age for 24 hours to obtain a clear and transparent PbTiO3 precursor solution. All operations were performed at room temperature and under dry conditions.

[0049] (2) Substrate cleaning

[0050] A Pt / Ti / SiO2 / Si multilayer substrate was used (a Pt layer, a Ti layer, a SiO2 layer, and a Si layer were stacked sequentially, with the Pt layer in contact with the subsequently grown ferroelectric thin film layer). The substrate was cut into 1 cm × 1 cm pieces and ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each, and then dried with nitrogen gas for later use.

[0051] (3) Preparation of perovskite-structured PbTiO3 ferroelectric thin film layer

[0052] The precursor solution was spin-coated onto a cleaned Pt / Ti / SiO2 / Si substrate at 3000 rpm for 30 seconds. It was then pyrolyzed at 300 °C for 10 minutes on a heating stage. This spin-coating-pyrolysis process was repeated 10 times (each spin-coating being 20 nm thick). The resulting stack was then placed in a muffle furnace and annealed at 700 °C at a rate of 5 °C / min for 30 minutes, followed by furnace cooling. TEM measurements showed that the total thickness of the annealed PbTiO3 ferroelectric thin film was approximately 200 nm.

[0053] (4) Formation of an amorphous protective layer

[0054] The same precursor solution was spin-coated again onto the annealed ferroelectric thin film surface (with the same spin-coating parameters), for a total of two spin-coatings. The film was then pyrolyzed at 200°C for 15 minutes on a heating stage, without further high-temperature annealing. Transmission electron microscopy (TEM) analysis showed that the thickness of the amorphous protective layer was approximately 40 nm.

[0055] The remanent polarization of the thin film prepared in this embodiment is 82 μC / cm. 2 .

[0056] Example 2

[0057] (The total thickness of the ferroelectric thin film is approximately 300 nm)

[0058] The preparation steps were the same as in Example 1, except that the spin-coating-pyrolysis process was repeated 15 times, and the total thickness of the ferroelectric thin film after crystallization annealing was approximately 300 nm. The protective layer formation conditions and determination method were the same as in Example 1. The remanent polarization of the obtained film was 152 μC / cm. 2 .

[0059] Example 3

[0060] (The total thickness of the ferroelectric thin film is approximately 400 nm)

[0061] The preparation steps were the same as in Example 1, except that the spin-coating-pyrolysis cycle was repeated 20 times, and the total thickness of the ferroelectric thin film after crystallization annealing was approximately 400 nm. The protective layer formation conditions and determination method were the same as in Example 1. The remanent polarization of the obtained film was 355 μC / cm.2 Electron microscopy characterization of the thin film revealed that the thickness of the amorphous protective layer was 40 nm.

[0062] Example 4

[0063] The preparation steps were the same as in Example 1, except that the spin-coating-pyrolysis process was repeated 23 times, and the total thickness of the ferroelectric thin film after crystallization annealing was approximately 460 nm. The remanent polarization of the resulting film was 500 μC / cm. 2 .

[0064] Comparative Example 1

[0065] (The total thickness of the ferroelectric thin film is approximately 200 nm, excluding the protective layer.)

[0066] The preparation steps are the same as in Example 1, except that step (4) of Example 1 is not included, i.e., no protective layer is formed. The thin film leakage current is severe, making it difficult to obtain a good hysteresis loop.

[0067] Comparative Example 2

[0068] (The total thickness of the ferroelectric thin film is approximately 300 nm, excluding the protective layer.)

[0069] The preparation steps are the same as in Example 2, except that step (4) of Example 2 is not included, i.e., a protective layer is not formed. The ferroelectric polarization intensity of the thin film is 60 μC / cm. 2

[0070] Comparative Example 3

[0071] (The total thickness of the ferroelectric thin film is approximately 400 nm, excluding the protective layer.)

[0072] The preparation steps are the same as in Example 3, except that step (4) of Example 3 is not included, i.e., a protective layer is not formed. The ferroelectric polarization of the thin film is 79 μC / cm. 2 .

[0073] Comparative Example 4

[0074] (The ferroelectric thin film layer is too thin)

[0075] The preparation steps are the same as in Example 1, except that the number of spin coatings in step (3) of Example 1 is reduced to 5. The thickness of the amorphous protective layer was measured to be approximately 100 nm by transmission electron microscopy. The reduction in the number of spin coatings in step (3) resulted in a lower film thickness, which led to significant leakage current and made it difficult to obtain a good hysteresis loop.

[0076] Comparative Example 5

[0077] (The ferroelectric thin film layer is too thick)

[0078] The preparation steps were the same as in Example 1, except that the number of spin-coating cycles in step (3) of Example 1 was increased to 45. The thickness of the amorphous protective layer was measured to be approximately 900 nm by transmission electron microscopy. The increased number of spin-coating cycles led to stress accumulation in the film, resulting in cracks.

[0079] Comparative Example 6

[0080] (The protective layer is too thin)

[0081] The preparation steps are the same as in Example 3, except that step (4) of Example 3, i.e., the number of spin-coating protective layers is reduced, and the spin-coating speed is increased. Specifically, the same precursor solution is spin-coated again on the annealed ferroelectric thin film surface at a spin-coating speed of 5000 rpm for 30 seconds, for a total of one spin-coating. Then, it is pyrolyzed at 200°C for 15 minutes on a heating stage, without further high-temperature annealing. The thickness of the resulting amorphous protective layer is approximately 5 nm. Because the obtained protective layer is too thin, it does not improve the performance of the thin film.

[0082] Comparative Example 7

[0083] (The protective layer is too thick)

[0084] The preparation steps are the same as in Example 3, except that step (4) of Example 3, i.e., the number of spin-coating protective layers is increased, the spin-coating speed is 3000 rpm, the time is 30 seconds, and a total of 4 spin-coatings are performed. The thickness of the resulting amorphous protective layer is approximately 80 nm. An excessively thick protective layer can suppress the intrinsic ferroelectric properties of the ferroelectric thin film.

[0085] Comparative Example 8

[0086] (The pyrolysis temperature of the protective layer is too low)

[0087] The preparation steps are the same as in Example 3, except that step (4) of forming the protective layer is to pyrolyze at 100°C for 15 minutes on a heating stage without high-temperature annealing. That is, the temperature of the protective layer is lower. Too low a pyrolysis temperature will result in incomplete removal of solvent and organic components from the film. Residual carbon impurities and pores will not only reduce the film density and bonding strength, but also increase leakage current, which is not conducive to obtaining a functional film with excellent performance.

[0088] Comparative Example 9

[0089] (The pyrolysis temperature of the protective layer is too high)

[0090] The preparation steps are the same as in Example 3, except that in step (4) of forming the protective layer, the protective layer is pyrolyzed at 500°C for 15 minutes on a heating stage without high-temperature annealing. That is, the temperature of the protective layer is relatively high. The excessively high pyrolysis temperature is close to the film crystallization temperature, which will induce the protective layer to over-crystallize, making it difficult to maintain the amorphous protective structure, and ultimately failing to achieve the design effect of improving the ferroelectric properties of the film.

[0091] Results Discussion

[0092] This invention investigates different film thicknesses, protective layer thicknesses, and protective layer pyrolysis temperatures for perovskite-structured PbTiO3 ferroelectric thin films, determining the optimal film thickness, pyrolysis temperature, and thickness for performance enhancement. When the thickness of the perovskite-structured PbTiO3 ferroelectric thin film is below 200 nm, the film exhibits significant leakage current; above 800 nm, cracks and stress problems arise. The thickness of the amorphous protective layer is 10–60 nm. Excessive thickness of the amorphous protective layer suppresses film polarity; conversely, insufficient thickness fails to enhance polarity. The amorphous protective layer is formed by pyrolysis of the precursor material at 120–400 °C. Within this temperature range, the organic components in the precursor decompose sufficiently but are insufficient to drive PbTiO3 crystallization, thus ensuring the protective layer remains amorphous. Ultimately, the remanent polarization of the composite structure of this invention is significantly improved.

[0093] Figure 1 The figures show the X-ray diffraction (XRD) patterns of the ferroelectric composite structures prepared in Examples 1 to 3 of this invention. As can be seen from the figures, the ferroelectric composite structures prepared in Examples 1 to 3 all exhibit clear perovskite diffraction peaks, including (001), (100), (101), (110), (002), (200), (210), and (211), indicating good crystallinity of the ferroelectric thin film layer. With increasing thickness, the (001) and (100) peaks show slight separation, and the axial ratio increases, which is beneficial to improving the ferroelectric performance.

[0094] Figure 2 This is a comparison diagram of the hysteresis loops (PE loops) of the structures obtained in Example 1 and Comparative Example 1 of the present invention. The thin film of Comparative Example 1 without a protective layer has a larger leakage current and a wider hysteresis loop; after adding an amorphous protective layer (i.e., Example 1), the leakage current is significantly reduced, the shape of the hysteresis loop tends to be rectangular, and the withstand voltage performance is improved.

[0095] Figure 3 This is a comparison diagram of the hysteresis loops (PE loops) of the structures obtained in Embodiment 2 and Comparative Example 2 of the present invention. After adding the protective layer, the residual polarization intensity is significantly improved, the coercive field is reduced, and the ferroelectric properties are comprehensively optimized.

[0096] Figure 4 This is a comparison diagram of the hysteresis loops (PE loops) of the structures obtained in Example 3 and Comparative Example 3 of the present invention. The film without a protective layer breaks down under an applied voltage of 20 V, with a residual polarization of only 79 μC / cm. 2 After modification with an amorphous protective layer, the residual polarization intensity jumped to 355 μC / cm. 2 And no breakdown occurred.

[0097] Figure 5 This is a spherical aberration electron microscope (TEM) image of the structure obtained in Example 3 of the present invention. Figure 5 The protective layer exhibits irregular and disordered contrast, and no periodic lattice fringes are visible, which are typical characteristics of an amorphous state. In contrast, a typical characteristic of a crystalline state is that, when magnified, the layer displays alternating bright and dark parallel lattice fringes and allows for the observation of neatly arranged atoms. Therefore, the protective layer of this invention possesses amorphous characteristics and is an amorphous protective layer. Figure 5 This demonstrates the crucial role of the amorphous protective layer in enhancing the pressure resistance and polarization intensity of thick films.

Claims

1. A ferroelectric composite structure, characterized in that, include: Perovskite-structured PbTiO3 ferroelectric thin film; as well as An amorphous protective layer is formed on the upper surface of the perovskite-structured PbTiO3 ferroelectric thin film layer. The protective layer is formed by pyrolysis of the precursor material used to form the perovskite-structured PbTiO3 ferroelectric thin film layer and is not subjected to crystallization annealing treatment.

2. The ferroelectric composite structure according to claim 1, wherein, The thickness of the perovskite-structured PbTiO3 ferroelectric thin film layer is 200–800 nm. Preferably, the thickness of the amorphous protective layer is 10–60 nm.

3. The ferroelectric composite structure according to claim 1, wherein, The amorphous protective layer is formed by pyrolysis of the precursor material at 120–400°C for 5–30 min.

4. The ferroelectric composite structure according to claim 1, wherein, The remanent polarization of the ferroelectric composite structure is 80-500 μC / cm. 2 .

5. The ferroelectric composite structure according to claim 1, further comprising a substrate, wherein the perovskite-structured PbTiO3 ferroelectric thin film layer is located on the substrate; Preferably, the substrate comprises a Pt layer, a Ti layer, a SiO2 layer and a Si layer stacked sequentially, wherein the Pt layer is in contact with the perovskite-structured PbTiO3 ferroelectric thin film layer.

6. A method for preparing the ferroelectric composite structure according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Provide a substrate; (2) A perovskite-structured PbTiO3 ferroelectric thin film layer is prepared on the substrate; (3) An amorphous protective layer is formed on the upper surface of the PbTiO3 ferroelectric thin film layer with the perovskite structure.

7. The method according to claim 6, wherein, Step (2) involves preparing a perovskite-structured PbTiO3 ferroelectric thin film layer on the substrate, which includes: (2-1) Spin-coat the precursor material for forming the PbTiO3 ferroelectric thin film layer of the perovskite structure onto the substrate, and perform pyrolysis treatment after each spin coating. Repeat the spin coating-pyrolysis process for a total of 1 to 30 spin coatings. (2-2) The obtained stack is subjected to crystallization annealing treatment to crystallize the ferroelectric thin film layer into a perovskite structure; Preferably, the pyrolysis temperature after each spin coating is 120–400°C, and the pyrolysis time is 5–30 min; Preferably, the crystallization annealing temperature is 650-750℃, and the crystallization annealing time is 25-50 min.

8. The method according to claim 6, wherein, Step (3) involves forming an amorphous protective layer on the upper surface of the perovskite-structured PbTiO3 ferroelectric thin film layer, which includes: The precursor material for forming the PbTiO3 ferroelectric thin film layer of the perovskite structure is spin-coated onto the PbTiO3 ferroelectric thin film layer of the perovskite structure, and then pyrolyzed at 120-400℃ for 5-30 min to form an amorphous protective layer, and no further crystallization annealing treatment is performed.

9. The method according to claim 7 or 8, wherein, The precursor material is formulated from lead acetate, tetrabutyl titanate, ethylene glycol methyl ether, deionized water, acetic acid, and formamide.

10. The application of the ferroelectric composite structure according to any one of claims 1 to 5 in the fabrication of ferroelectric memories, ferroelectric logic devices or low-power electronic devices.